Development of Data Acquisition System Using LabVIEW-based Interface for Aircraft Application - Mujaahid, Faaris; Anjasmara, Fuad Hammaminata Arya; Wiyagi, Rama Okta; Putra, Karisma Trinanda (Journal of Electrical Technology UMY, 2018)
This paper discusses an interface data acquisition (DAQ) of a rocket using LabVIEW. The software development is meant to improve the quality and reliability of the interface that has been built by the UMY rocket team. The data used on the experiments is a set of dummy data created for simulation purpose. This data is generated by Arduino UNO, in which it was acquired by LabVIEW through VISA serial communication platform. The test results show that there is 10% error during the data retrieval. The DAQ average speed is 270 milliseconds. This new approach has more stable and reliable system when compared to previous algorithm.